Reframing scarcity through social thermodynamics and Islamic ethics: An interdisciplinary conceptual approach - Sujata, Tatang (UIN Sunan Gunung Djati Bandung, 2025)
This metatheoretical study emerges from a critical reassessment of classical economic thought, which reduces scarcity to a mere technical issue of limited resources against unlimited wants—neglecting its deeper social, ecological, and ethical dimensions. In the face of accelerating global crises marked by structural inequality, institutional decay, and environmental degradation, scarcity is better understood as a manifestation of rising social entropy—a systemic disintegration triggered by the depletion of social energy such as trust, participation, and moral legitimacy. This research aims to reframe scarcity through an interdisciplinary synthesis of social entropy theory (Bailey), social thermodynamics modeling (Tsekov), and foundational Islamic ethical principles including ‘adl (justice), amanah (trust), and mīzān (cosmic balance). Using a conceptual literature review, this study develops a theoretical framework that positions ethical and spiritual values as vital forms of social energy capable of counteracting entropy and sustaining systemic equilibrium. The findings reveal that scarcity is not simply a material deficiency but a multidimensional crisis demanding a transformative response—one rooted not only in technical rationality but also in spiritual wisdom, distributive justice, and collective moral responsibility. The study contributes a novel conceptual model that bridges physical social science with Islamic moral epistemology, offering a holistic lens for understanding scarcity while informing equitable public policy, institutional reform, and sustainable social design.